ANALISIS KEMAMPUAN ARGUMENTASI SISWA PADA MATERI FUNGSI DI KELAS VIII SMP NEGERI 6 PALU : Analysis Of Argumentation Ability Students On Functional Materials In Class VIII Smp Negeri 6 Palu - Dewi, Arum Resiana; Idris, Mustamin; Rizal, Muh.; Sugita, Gandung (Jurnal Elektronik Pendidikan Matematika Tadulako, 2024)
The aim of this study was to obtain a description of the analysis of the argumentation abilities of class VIII students at SMP Negeri 6 Palu on function. This type of research is descriptive research type. The approach used in this study is a qualitative approach. The subjects of this study were three students in grade VIII of SMP Negeri 6 Palu for the 2021/2022 academic year. Students at a high level of mathematical ability have good argumentation skills because they are able to state what information is in the problem and at each step of completion (Data), are able to provide statements to solve a problem (Claim), are able to show data as well as provide evidence that is able to support statement put forward (Warrant), and able to reject the statement and explain the conditions under which the statement is not valid (Disclaimer). Students at the moderate level of mathematical ability have fairly good argumentation skills because they are able to provide statements to solve a problem (Claim), are able to show data as well as provide evidence that is able to support the statements put forward (Warrant). Students at low ability levels have less argumentation skills because they have not provided enough information about what is in the problem and at each step of completion (Data), have not been able to provide statements to solve a problem (Claim), have not been able to provide evidence capable of supporting statements made stated (Warrant), and also has not been able to provide an explanation of the conditions under which the statement is not valid (Rebuttal).